Pengaruh Modal Sosial Dan Orientasi Kewirausahaan Terhadap Strategi Harga Pada Umkm - Laoli, Alex Putra Berkat; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2026)
This research aims to analyze the influence of social capital and entrepreneurial orientation on pricing strategies among MSME actors. The research method employed is a quantitative approach using multiple linear regression analysis to test the relationships between variables. The results indicate that social capital plays a crucial role in determining price flexibility, while entrepreneurial orientation drives innovation in competitive pricing. In conclusion, the integration of strong social networks and risk-taking behavior is vital for business sustainability in dynamic markets. This abstract provides a general description without the use of citations or unfamiliar technical terms.